Implementasi pemberian reward pada pembelajaran matematika di kelas V MIN 2 Kota Palembang - Toyba Tulilah; Fuaddilah Ali Sofyan; Nurlaeli Nurlaeli (Universitas Muhammadiyah Ponorogo, 2020)
Reward is basically a response given by the teacher to the behavior or deeds of students who are considered positive, and cause recurrence or increase the behavior. The results of the study show that the teacher has applied a reward (1) Implementation of a reward in Mathematics learning in VA class that has implemented a reward using words of praise,